Metastasizing leiomyoma during pregnancy - Jéssica Souto Morlin; Altivo Manoel Luiz Neto; Anelise Mendes Melo; Marina Carvalho Paschoini; Luis Ronan Marquez Ferreira de Souza; João Henrique do Amaral; Eddie Fernando Candido Murta; Rosekeila Simões Nomelini (Clinical and Biomedical Research, 2023)
Uterine leiomyoma is a benign tumor of myometrial tissue which affects women of reproductive age. Its prevalence increases with age and has a peak incidence at the age of forty. The term “metastasizing leiomyoma” refers to a tumor of dense connective tissue and smooth myometrial muscle cells located outside the uterus. This group of tumors can metastasize to different organs, the lung being its main focus. We present the case report of a 33-year-old female gravida 3, para 1, abortus 1, at 11 weeks of pregnancy, with pelvic masses. The diagnosis was metastasizing leiomyoma during pregnancy.